Unified Power Quality Conditioner Model Based with Series and Shunt Filters - khalaf Gaeid; Mounir T. Hamood (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
With the increase of the complexion in the power distribution system, it is very possible that several kinds of power quality disturbances are happened in a power distribution system simultaneously.This paper proposes a unified power quality conditioner (UPQC) including a series and a shunt active power filter (APF) to compensate harmonics in both the distorted supply voltage and nonlinear load current. In the series APF control scheme, a proportional-integral (PI) controller , meanwhile a PI controller and are designed in the shunt APF control scheme to relieve harmonic currents produced by nonlinear loads. The DC voltage is maintained constant using Two degree of freedom proportional integral voltage controller(2DoFPI). The performance of the proposed UPQC is significantly improved compared to the conventional control strategy. The feasibility of the proposed UPQC control scheme is validated through the simulations.